Założenia zaktualizowanego polskiego programu konwergencji i ich znaczenie na drodze do euro - Michalczyk, Wawrzyniec (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article deals with the contents of the new Convergence programme published by Polish government in 2006. The author analyzes the role of main macroeconomic indicators for the probability of Poland's accession to the euro zone. Different prognoses of economic situation are compared. The main conclusion is that the Polish economy is going to fulfil the convergence criteria by the end of the decade and in consequence Poland may be then ready for the adoption of the euro. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 227-235